Targeting histone deacetylase 6 mediates a dual anti‐melanoma effect: Enhanced antitumor immunity and impaired cell proliferation. Issue 7 (24th April 2015) - Woan, K.V.; Lienlaf, M.; Perez-Villaroel, P.; Lee, C.; Cheng, F.; Knox, T.; Woods, D.M.; Barrios, K.; Powers, J.; Sahakian, E.; Wang, H.W.; Canales, J.; et al.
Abstract : The median survival for metastatic melanoma is in the realm of 8–16 months and there are few therapies that offer significant improvement in overall survival. One of the recent advances in cancer treatment focuses on epigenetic modifiers to alter the survivability and immunogenicity of cancer cells. Our group and others have previously demonstrated that pan‐HDAC inhibitors induce apoptosis, cell cycle arrest and changes in the immunogenicity of melanoma cells. Here we interrogated specific HDACs which may be responsible for this effect. We found that both genetic abrogation and pharmacologic inhibition of HDAC6 decreases in vitro proliferation and induces G1 arrest of melanoma cell lines without inducing apoptosis. Moreover, targeting this molecule led to an important upregulation in the expression of tumor associated antigens and MHC class I, suggesting a potential improvement in the immunogenicity of these cells. Of note, this anti‐melanoma activity was operative regardless of mutational status of the cells. These effects translated into a pronounced delay of in vivo melanoma tumor growth which was, at least in part, dependent on intact immunity as evidenced by the restoration of tumor growth after CD4+ and CD8+ depletion. Given our findings, we provide the initial rationale for the further development of selective HDAC6 inhibitors as potential therapeutic anti‐melanoma agents. Highlights: Inhibition of HDAC6 results in cell cycle arrest. Targeting HDAC6 upregulates expression of tumor associated antigens. In vivo anti‐tumor activity of HDAC6 disruption requires intact immunity. HDAC6 represents a novel molecular target for the treatment of melanoma.